Perancangan Sistem Informasi Akademik Digital Berbasis Web di SD Nayu Barat II Surakarta - Khaidir Umar; Octa Novalinda; Ina Sholihah Widiati (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Nayu Barat II Public Elementary School is one of the public elementary schools in Banjarsari District. SD Negeri Nayu Barat II is located on Jl. Majapahit I No. 21, RT. 08/RW. 14, Nusukan, District. Banjarsari, Surakarta City. So far, information at SD Negeri Nayu Barat II is still provided in printed form. Students can easily find out information about SD Negeri Nayu Barat II apart from using information books, so they are trying to create another alternative by creating a website, apart from that, students are expected to be able to access information easily and efficiently. This website was created using WordPress with other supporting software, namely Apache Server. Apache is the name of a web server that is responsible for HTTP request-response and logging detailed information. Apart from that, Apache is also defined as a web server that is compact, modular, follows the HTTP protocol standard, and is of course very popular. The result of this final assignment is a web-based information system. By creating a web-based information system and implementing it in the process of disseminating school information, it is easy for parents/guardians to access it and gives the principal confidence to educate their children.